Unprecedented directed lateral lithiations of tertiary carbons on NHC platforms12. Issue 15 (20th November 2014) - Danopoulos, Andreas A.; Braunstein, Pierre; Rezabal, Elixabete; Frison, Gilles
Abstract : Deprotonation of the tautomeric mixture of 4-amido-imidazoliums and 4-amino-N-heterocyclic carbenes led to dilithiated dianionic functional NHCs, via an unprecedented regioselective, directed remote lateral lithiation of a tertiary C HMe2 carbon. DFT calculations support that the nature of products is under thermodynamic control. Abstract : Unexpected and unprecedented directed remote lateral lithiation at one CH(CH3 )2 of the 3-(2, 6-di-isopropylphenyl) wingtip took place upon the reaction of functionalised N-heterocyclic carbene-type molecules with excess of LiCH2 SiMe3, leading to dilithiated dianionic 4-amido-N-heterocyclic carbenes. DFT calculations show that the nature of the isolated species are under thermodynamic control.